REPRESENTASI CITRA BASUKI TJAHAJA PURNAMA DALAM VIDEO BLOG (VLOG) PADA CHANNEL YOUTUBE PANGGIL SAYA BTP VERSI #1-PULANG - Hariyono Suyono; Nita Rimayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Presenting ourselves in an effort to shape the current self-image becomes very important for every individual, this we can see by observing the environment around us. Where every individual seeks to share each of his activities with others with the aim that people acknowledge so as to form his own image. The presence of YouTube in the midst of society brings many changes where in addition to being a media information YouTube is utilized as a medium of self-presentation or the process of forming self-identity. So that the presence of YouTube has given freedom for anyone be it artists, students, or political figures who want to present themselves through YouTube media. Basuki Tjahaja Purnama is one of the political figures who used YouTube as a means to form his self-image, where the first video uploaded via his personal channel received appreciation from the public, marked the number of video viewers. This study aims to determine how the image representation of Basuki Tjahaja Purnama in the video blog (vlog) on the youtube channel called me btp version # 1-return.               This study uses a qualitative method with semiotic analysis of Roland Barthes. The subject in this research is the video blog (vlog) on the youtube channel, call me btp version # 1-return, while the object in this study is audio and visual in the video blog (vlog) on the youtube channel, call me btp version # 1- return. In this study using documentation and observation data collection techniques. To achieve the validity of the data in this study the authors used triangulation.                The results of this study indicate the meaning of denotation contained in the video blog (vlog) on the youtube channel, call me btp version # 1-return based on what is displayed directly. The meaning of the connotation of the results of the analysis of the implied meaning contained in the dialogue, as well as the hidden meaning that is stored behind what is displayed in the video. The semiotic myth contained in the video blog (vlog) on the youtube channel called me btp version # 1-return is a common myth that is in the midst of society and is still believed to this day. The representation of the image of Basuki Tjahaja Purnama in the video blog (vlog) on the youtube channel called me btp version # 1-return shows a positive image or a good image of Basuki Tjahaja Purnama such as caring, assertive, loyalty, open, simple, honest and responsible Keywords: Image, Vlog, Semiotics